(3x − 5) − (4x + 6)
Pretend that there is a 1 in front of the first bracket.
Pretend that there is a -1 in front of the second bracket.
Multiply the first bracket by 1
(1)(3x)=3x, (1)(-5)=-5
Multiply the second bracket by -1
(-1)(4)=-4, (-1)(6)=-6
3x-5-4x-6
3x-4x-5-6 ( combine like terms)
-x-11
Answer: -x-11 or -11-x
Answer:
![f(x)=0.7(5)^x](https://tex.z-dn.net/?f=f%28x%29%3D0.7%285%29%5Ex)
Step-by-step explanation:
![\text{Exponential function: }y=a\cdot b^x](https://tex.z-dn.net/?f=%5Ctext%7BExponential%20function%3A%20%7Dy%3Da%5Ccdot%20b%5Ex)
It is two types of function.
- Exponential Growth: If function increase as value of x increase.
In this case, a>0 and b>1
- Exponential decay: If function decrease as value of x increase.
In this case, a>0 and 0<b<1
We need to choose exponential growth function.
![\text{Exponential Growth function: }f(x)=0.7(5)^x](https://tex.z-dn.net/?f=%5Ctext%7BExponential%20Growth%20function%3A%20%7Df%28x%29%3D0.7%285%29%5Ex)
Here a=0.75>0 and b=5>1
Therefore, This function is exponential growth.
Answer:
BE = FC = 3 inches, EF = 2 inches
Step-by-step explanation:
The sum of angles A and D is 180°, so the sum of their half-angles is 90°. That is, half of A plus half of B add to 90°, so the bisector from B intersects AE at a right angle. Call that point of intersection X.
Then angle ABX = angle EBX, so triangle ABX is congruent to triangle EBX. Sides AB and BE are corresponding sides of congruent triangles.
The same argument applies to sides DC and CF.
Thus we have BE = CF = 3 inches, and EF is the left-over distance, 2 inches.
Answer:
D (We can extend all the expressions)
You doing virtual school too